The Role of Groups Reference, Perceived Value, and Customer Relationship Marketing on Product Purchasing Decisions in the Shopee Marketplace - Fahmi, Syaifuddin (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2025)
This study aims to analyze the influence of reference group, perceived value, and customer relationship marketing on product purchasing decisions in the Shopee marketplace. These three independent variables were selected based on their importance in shaping digital consumer behavior, particularly among the younger generation who actively use social media and e-commerce platforms. This study employed a quantitative approach with multiple linear regression analysis. The sample size was 200 respondents, active Shopee users residing in Malang City. The sampling technique used purposive sampling, with the criteria being that respondents were at least 17 years old and had made at least two purchases on Shopee in the past three months. Data collection was conducted through an online questionnaire that had been tested for validity and reliability.The results of the regression analysis indicate that simultaneously, the variables reference group, perceived value, and customer relationship marketing significantly influence purchasing decisions with a significance value <0.05. Partially, the reference group variable has a significant positive effect on purchasing decisions, with the regression coefficient indicating that references from social groups such as friends, family, or online communities have a significant influence on consumer preferences in selecting products on Shopee. The perceived value variable also had a significant influence, indicating that consumer perceptions of product value (quality, price, and benefits) influenced satisfaction levels and purchasing decisions. Meanwhile, customer relationship marketing, which encompasses Shopee's efforts to maintain customer relationships through promotions, personalized services, and loyalty programs, also positively contributed to consumer purchasing decisions.These findings indicate that marketing strategies that consider social aspects, perceived customer value, and long-term relationships with consumers are crucial for increasing sales conversions on e-commerce platforms. The practical implications of this research can serve as a basis for Shopee's business owners and marketing managers to design a more segmented and personalized approach. For example, this could include optimizing user community features, strengthening product reviews and recommendations, and improving the quality of loyalty programs and relevant communications. Thus, this research contributes to the digital marketing literature and provides empirical insights for marketplaces and MSMEs selling their products through platforms like Shopee. This research also recommends that further studies expand the scope and consider other variables such as brand trust and service quality to more comprehensively understand digital consumer purchasing behavior.Keywords: Reference Group, Perceived Value, Customer Relationship Marketing, Purchasing Decision, Shopee Marketplace